Assessment and clinical validation of margins for adaptive simultaneous integrated boost in neo-adjuvant radiochemotherapy for rectal cancer. Issue 2 (March 2015) - Raso, Roberta; Scalco, Elisa; Fiorino, Claudio; Broggi, Sara; Cattaneo, Giovanni Mauro; Garelli, Stefania; Pagliazzi, Marco; Slim, Najla; di Muzio, Nadia; Rizzo, Giovanna; Calandrino, Riccardo; Passoni, Paolo
Abstract: Purpose: An adaptive concomitant boost (ACB) for the neo-adjuvant treatment of rectal cancer was clinically implemented. In this study population margins M(90, 90) considering rectal deformation were derived for 10 consecutive patients treated at 18 × 2.3 Gy with Helical Tomotherapy (HT) and prospectively validated on 20 additional patients treated with HT, delivering ACB in the last 6 fractions. Methods: Sectorial margins M(90, 90) of the whole and second treatment parts were assessed for 90% population through a method combining the 90% coverage probability maps of rectal positions (CPC90%) with 3D local distance measurements between the CPC90% and a reference rectal contour. M(90, 90) were compared with the margins M(90, 90) 95%/99%, ensuring CPC90% coverage with 95%/99% confidence level. M(90, 90) of the treatment second part were chosen as ACB margins which were clinically validated for each patient by means of %volume missing of CPC5/6 excluded by the ACB margins. Results: The whole treatment M(90, 90) ranged between 1.9 mm and 9 mm in the lower-posterior and upper-anterior sectors, respectively. Regarding ACB, M(90, 90) were 7 mm in the anterior direction and <5 mm elsewhere. M(90, 90) 95%/99% did not significantly differ from M(90, 90). The %volume excluded by the ACB margin was<2% for all male and <5% for 9/10 female patients. The dosimetry impact on R_adapt for the patients with the largest residual error was negligible. Conclusions: Local deformation measurements confirm an anisotropic motion of rectum once set-up error is rigidly corrected. Margins of 7 mm anterior and 5 mm elsewhere are adequate for ACB. Female patients show a slightly larger residual error. Highlights: Rectal motion during adaptive concomitant boost (ACB) for rectal cancer is an issue. Based on daily MVCT data of 10 pts, margins for rectum deformation were assessed. Smaller margins were assessed in the 2nd half of treatment (when ACB is delivered). Margins for ACB (5–7 mm) were successfully validated on 20 new patients. Female patients show a slightly larger residual (deformation) error than males.